A vez dos independentes(?): um olhar sobre a produção musical independente do país - Vicente, Eduardo (2006)
This paper aims at discussing the development of Brazilian independent musical production, throughout the analysis of what I consider its three main points of articulation: the late 70’s scene, which was marked by the actuation of the musician and producer Antonio Adolfo and by the production that emerged from Lira Paulistana theater (São Paulo); the 90’s scene, that was boasted by the evolution of the digital technologies for production and the Majors’ outsourcing strategies; and the present moment of a never seen articulation of the independent scene, as well its autonomous performance in different musical segments.